ANALYSIS OF RISK FACTORS ASSOCIATED WITH DEPRESSION IN ELDERLY LEPROSY SURVIVORS IN TUBAN REGENCY: Analisis Faktor Risiko Yang Berhubungan Dengan Depresi Pada Lansia Penyintas Kusta di Kabupaten Tuban - Jannatul Kamilah, Itsna; Mudia Sari, Ulfa; Yovita Hendrati, Lucia (Universitas Airlangga, 2025)
Background: Leprosy is an infectious disease that has an impact on the physical, socioeconomic, spiritual, and psychological of sufferers with one example being depression. Purpose: This research aims to find the relationship between risk factors and depression in elderly leprosy survivors residing at the Leprosy Rehabilitation Center, Tuban. Methods: The research method used is analytical observational with a cross-sectional approach. The research population consists of 100 leprosy survivors at the Social Rehabilitation Unit for People with Chronic Illnesses, Nganget, Tuban. The total sample of the research is 64 respondents selected from the population using simple random sampling technique. The data analysis technique employed is the Chi-square test. Results: Most of the respondents had level 2 disability as much as 68.80% and as much as 65.50% experienced depression. The research findings indicate a relationship between the variables of gender (p=0.03; PR=1.49; 95% CI=1.00-2.21), level of disability (p=0.00; PR=2.26; 95% CI=1.08-4.71), disease perception (p=0.00; PR=2.05; 95% CI=1.27-3.31), self-stigma (p=0.00; PR=2.00; 95% CI=1.32-3.02), with depression among elderly leprosy survivors. Conclusion: The conclusion indicates that the factors of gender, level of disability, self-stigma, and disease perception have a significant relationship with depression in elderly leprosy survivors, while the factors of age, education level, and caregiver support are not related to depression in elderly leprosy survivors.